Human Folate Receptor-1 Gene Expression and Correlation with Physiological Leptin hormone in Obese and Non-obese Subjects (Medico Legal Update, 2021)
Background: One of the most important agents that must be found in all dividing cells is folate.Aim: Assessment of human folate receptor-1 gene expression and correlation with leptin hormone in obeseand non-obese subjectsof Babylon province, Iraq.Subjects and Method: This study included 60 obese subjects (OS) in the range of age (10-45 years) and 30normal weight subjects (NOS) in range age of (11-43 years). FOR-1 gene expression were assessing by qRTPCR after RNA extraction from fresh blood of all obese and normal subjects and immediately convertinginto cDNA. Leptin was assessed by ELISA method.Results: The results suggesting that founds the positive correlation (r2=0.447) between ages of OS andlevels of LEP (ng/ml). The results of this study showed significant differences (p-value< 0.05) in levels ofleptin (LEP) between OS and NOS groups. The results showing that the FOR-1 gene expression ratio inNOS compare to expression OS were 11.9 and 7.1.Conclusion: FOR-1 have a higher expression in OS compare to NOS and this may be useful in diagnosticand therapeutic tools in diseases or cancers in OS.